Customer experience challenges: bringing together digital, physical and social realms. (7th September 2018) - Bolton, Ruth N.; McColl-Kennedy, Janet R.; Cheung, Lilliemay; Gallan, Andrew; Orsingher, Chiara; Witell, Lars; Zaki, Mohamed
Abstract : Purpose: The purpose of this paper is to explore innovations in customer experience at the intersection of the digital, physical and social realms. It explicitly considers experiences involving new technology-enabled services, such as digital twins and automated social presence (i.e. virtual assistants and service robots). Design/methodology/approach: Future customer experiences are conceptualized within a three-dimensional space – low to high digital density, low to high physical complexity and low to high social presence – yielding eight octants. Findings: The conceptual framework identifies eight "dualities, " or specific challenges connected with integrating digital, physical and social realms that challenge organizations to create superior customer experiences in both business-to-business and business-to-consumer markets. The eight dualities are opposing strategic options that organizations must reconcile when co-creating customer experiences under different conditions. Research limitations/implications: A review of theory demonstrates that little research has been conducted at the intersection of the digital, physical and social realms. Most studies focus on one realm, with occasional reference to another. This paper suggests an agenda for future research and gives examples of fruitful ways to study connections among the three realms rather than in a single realm. Practical implications: This paper provides guidance for managers in designing and managing customer experiences that the authors believe will need to be addressed by the year 2050. Social implications: This paper discusses important societal issues, such as individual and societal needs for privacy, security and transparency. It sets out potential avenues for service innovation in these areas. Originality/value: The conceptual framework integrates knowledge about customer experiences in digital, physical and social realms in a new way, with insights for future service research, managers and public policy makers.